High-performance microcrystalline glass based on multi-source solid waste and preparation method of high-performance microcrystalline glass

By crushing, drying, ball milling, sieve and mixing, water quenching and sintering, high-performance microcrystalline glass is prepared, which solves the problem of low solid waste disposal and resource utilization efficiency and achieves efficient resource utilization.

CN119638200AActive Publication Date: 2025-03-18SOUTHWEST PETROLEUM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411766362.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively dispose of and utilize oil-bed rock degreasing residues and phosphorus slags, resulting in poor disposal of these solid wastes and low resource utilization efficiency.

Method used

By obtaining oil-bed rock chip deoilation degreasing residues and phosphorus residues, crushing, drying, ball milling and sieving, mixing, melting, water quenching and sintering, high-performance CaO-Al2O3-SiO2(CAS) microcrystalline glass or CaO-MgO-Al2O3-SiO2(CMAS) microcrystalline glass.

Benefits of technology

The high-value utilization of oil-bed rock chip degreases and phosphorus slags has been achieved, and the microcrystalline glasses are excellent in performance, meet the standard requirements of industrial microcrystalline sheets, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638200A_ABST
    Figure CN119638200A_ABST
Patent Text Reader

Abstract

The invention discloses high-performance microcrystalline glass based on multi-source solid waste and a preparation method thereof.The preparation method comprises the following steps that S1, oil-based rock debris deoiling residues and phosphorus slag are obtained, and the oil-based rock debris deoiling residues and the phosphorus slag are crushed, dried, ball-milled and sieved respectively to obtain residue powder and phosphorus slag powder; s2, component detection is conducted on the phosphorus slag powder, and the content of MgO in the phosphorus slag powder is determined; uniformly mixing the residue powder, the phosphorus slag powder and fly ash according to a detection result, and melting to obtain basic glass liquid; s3, performing water quenching on the basic glass liquid to obtain basic glass, and performing drying, ball milling and sieving on the basic glass to obtain basic glass powder; and S4, preparing the basic glass powder into a glass ceramic original sample, sintering the glass ceramic original sample, and naturally cooling to obtain the high-performance glass ceramic. According to the method, the high-performance glass ceramics can be prepared by cooperating with two solid wastes, namely the oil-based rock debris deoiling residues and the phosphorus slag, and synergistic high-value utilization of the multi-source solid wastes is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of collaborative high-value resource utilization of multi-source solid waste, and in particular to a high-performance microcrystalline glass based on multi-source solid waste and a preparation method thereof. Background Art

[0002] As a solid waste generated by horizontal drilling with oil-based mud, the oil content of oil-based cuttings is as high as 15-25%, which belongs to the "HW08 Waste Mineral Oil Category" in the "National List of Hazardous Wastes". Pyrolysis technology treats oil-based cuttings with high-temperature thermal decomposition under anoxic or anaerobic environment conditions, so that the oil content of the oil-based cuttings after pyrolysis treatment is reduced to less than 1%. Although pyrolysis technology solves the problem of mineral oil recovery from oil-based cuttings, there is still a problem of the disposal of the de-oiled residues of the treated oil-based cuttings. Traditional oil-based cuttings de-oiling residues are mainly used to prepare sintered bricks and cement, but the low value of the product affects the willingness to recycle the resources, resulting in a blocked resource recovery path.

[0003] In addition, phosphorus slag is an industrial solid waste generated in the phosphorus chemical production process, which mainly comes from the production of yellow phosphorus. Every ton of yellow phosphorus produced generates about 8 to 10 tons of phosphorus slag. The annual amount of phosphorus slag produced in my country exceeds 7 million tons, and the utilization rate is less than 50%.

[0004] Therefore, how to dispose of these solid wastes or even coordinate the utilization of these solid wastes as high-value resources is a technical problem that urgently needs to be solved. Summary of the invention

[0005] In view of the above problems, the present invention aims to provide a high-performance microcrystalline glass based on multi-source solid waste and a preparation method thereof.

[0006] The technical solution of the present invention is as follows:

[0007] On the one hand, a method for preparing high-performance glass-ceramics based on multi-source solid waste is provided, comprising the following steps:

[0008] S1: obtaining oil-based rock cuttings deoiling residue and phosphorus slag, and crushing, drying, ball milling and sieving the oil-based rock cuttings deoiling residue and the phosphorus slag respectively to obtain residue powder and phosphorus slag powder;

[0009] S2: performing component detection on the phosphorus slag powder to confirm the content of MgO in the phosphorus slag powder;

[0010] If the content of MgO in the phosphorus slag powder is less than 15% of the total mass of the phosphorus slag powder, the residual powder and the phosphorus slag powder are mixed, and after being evenly mixed, they are melted to obtain a basic glass liquid;

[0011] If the content of MgO in the phosphorus slag powder is less than 25% and greater than or equal to 15% of the total mass of the phosphorus slag powder, the residual powder and the phosphorus slag powder are mixed with fly ash, and the mixture is uniformly mixed and then melted to obtain a basic glass liquid;

[0012] S3: quenching the basic glass liquid to obtain basic glass, and drying, ball-milling and sieving the basic glass to obtain basic glass powder;

[0013] S4: placing the basic glass powder in a mold and obtaining a glass-ceramic sample through a sample making machine, sintering the glass-ceramic sample, and obtaining the high-performance glass-ceramic after natural cooling.

[0014] Preferably, in step S1, a sieve with a mesh size of 200 or more is used for screening.

[0015] Preferably, in step S2, when mixing, the amounts of the raw materials used are 10-90 parts of residue powder, 10-50 parts of phosphorus slag powder, and 0-50 parts of fly ash, respectively, by weight.

[0016] Preferably, in step S2, during melting, the temperature is raised to 1350-1450°C at a rate of 5-7°C / min and kept at this temperature for 150-180 min.

[0017] Preferably, in step S3, water quenching is performed by immersion water quenching.

[0018] Preferably, in step S3, when water quenching is performed, the quenching is performed in cold water at 10-20° C. for 5-10 min; when drying is performed, the quenching is performed at 100-105° C. for 2-3 h.

[0019] Preferably, in step S3, screening is performed using a sieve with a mesh size of 200 or more.

[0020] Preferably, in step S4, when preparing the original sample of the microcrystalline glass, 0.5-1 mL of anhydrous ethanol or deionized water is added to the mold, and the mold is pressed for 10-15 seconds under a pressure of 8-10 MPa to obtain the original sample of the microcrystalline glass.

[0021] Preferably, in step S4, the sintering is performed at 700-900° C. for 120-180 min.

[0022] On the other hand, there is also provided a high-performance microcrystalline glass based on multi-source solid waste, which is prepared by using any one of the above-mentioned methods for preparing high-performance microcrystalline glass based on multi-source solid waste.

[0023] The beneficial effects of the present invention are:

[0024] (1) The present invention utilizes the de-oiling residue of oil-based rock cuttings as the raw material for sintering a high-performance microcrystalline glass, and at the same time assists phosphorus slag in treating "waste" with "waste", thereby achieving the coordinated high-value utilization of multi-source solid waste and solving the disposal problem of the de-oiling residue of oil-based rock cuttings and phosphorus slag.

[0025] (2) The present invention can adjust the raw material ratio according to the different MgO contents in the phosphorus slag to prepare CaO-Al2O3-SiO2 (CAS) glass-ceramics and CaO-MgO-Al2O3-SiO2 (CMAS) glass-ceramics.

[0026] (3) The present invention can successfully prepare CAS-based microcrystalline glass and CMAS-based microcrystalline glass without using any additional nucleating agent, and the various properties of these microcrystalline glasses meet the requirements of the standard "Industrial Microcrystalline Plate" (JC / T2097-2011), and are far higher than the lower limit of the requirements in the standard.

[0027] (4) The present invention uses phosphorus slag as a raw material to provide MgO, which can prepare CAS series glass-ceramics and CMAS series glass-ceramics at a lower sintering temperature; and the prepared CMAS series glass-ceramics have better performance and a lower sintering temperature than the glass-ceramics prepared using pure MgO reagent.

[0028] (5) The preparation process of the present invention is scientific and reasonable, the processing steps are simple and easy, and the cost is relatively low; large-scale production and processing can be achieved to generate economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the technical description will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creativity and labor.

[0030] Figure 1 It is a schematic flow chart of the method for preparing high-performance microcrystalline glass based on multi-source solid waste according to the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0032] On the one hand, if Figure 1 As shown, the present invention provides a method for preparing high-performance microcrystalline glass based on multi-source solid waste, comprising the following steps:

[0033] S1: Obtain oil-based rock cuttings de-oiling residue and phosphorus slag, and crush, dry, ball-mill and sieve the oil-based rock cuttings de-oiling residue and the phosphorus slag to obtain residue powder and phosphorus slag powder.

[0034] In a specific embodiment, a sieve with a mesh size of 200 or more is used for sieving. It should be noted that the mesh size of the sieve in this embodiment is only the preferred mesh size of the present invention. The higher the mesh size, the finer the powder obtained. The fineness of different raw materials will affect the contact area between particles, and then affect the diffusion of particles during sintering, which ultimately leads to differences in the density of the microcrystalline glass structure. The finer the powder, the more beneficial it is to the performance of the microcrystalline glass.

[0035] S2: performing component detection on the phosphorus slag powder to confirm the content of MgO in the phosphorus slag powder;

[0036] If the content of MgO in the phosphorus slag powder is less than 15% of the total mass of the phosphorus slag powder, the residual powder and the phosphorus slag powder are mixed, and after being evenly mixed, they are melted to obtain a basic glass liquid;

[0037] If the content of MgO in the phosphorus slag powder is less than 25% and greater than or equal to 15% of the total mass of the phosphorus slag powder, the residual powder and the phosphorus slag powder are mixed with fly ash, and then melted to obtain basic glass liquid after mixing evenly.

[0038] It should be noted that the method of conducting component detection on phosphorus slag powder to confirm the MgO content therein is an existing technology, and the specific detection method will not be repeated here.

[0039] In a specific embodiment, when mixing, the amount of each raw material used is 10-90 parts of residue powder, 10-50 parts of phosphorus slag powder, and 0-50 parts of fly ash, respectively, by weight.

[0040] In the above embodiment, when the amount of fly ash is 0 parts, that is, the basic glass liquid only contains residual powder and phosphorus slag powder, the microcrystalline glass obtained subsequently prepared is CAS series microcrystalline glass; when the amount of fly ash is not 0 parts, that is, the basic glass liquid contains not only residual powder and phosphorus slag powder but also fly ash, the microcrystalline glass obtained subsequently prepared is CMAS series microcrystalline glass.

[0041] In a specific embodiment, when melting, the temperature is raised to 1350-1450°C at a rate of 5-7°C / min and kept at this temperature for 150-180 minutes. It should be noted that there is no difference in the performance of the sample obtained by slowly heating the temperature to the target temperature and directly placing the mixture at the target temperature, but it is more convenient and easier to melt the sample by slowly heating the sample to the target temperature.

[0042] S3: quenching the basic glass liquid to obtain basic glass, and drying, ball-milling and sieving the basic glass to obtain basic glass powder.

[0043] In a specific embodiment, the immersion water quenching method is used for water quenching. In this embodiment, the immersion water quenching method is used for water quenching. The method is simple and easy to implement, and the temperature of the immersion water quenching rapid cooling can make the base glass have a more uniform structure and stronger physical properties.

[0044] In a specific embodiment, when water quenching is performed, the quenching is performed in cold water at 10-20° C. for 5-10 minutes; when drying is performed, the quenching is performed at 100-105° C. for 2-3 hours.

[0045] In a specific embodiment, the sieving is performed using a sieve with a mesh size of 200 or more. In a specific embodiment, the basic glass powder obtained by ball milling and passing through sieves with different apertures has an aperture range of 0.075 to 0.25 mm.

[0046] It should be noted that the mesh size of the sieve in the above embodiment is only the preferred mesh size of the present invention. The higher the mesh size, the finer the powder obtained. The fineness of different raw materials will affect the contact area between particles, and then affect the diffusion of particles during sintering, which ultimately leads to differences in the density of the microcrystalline glass structure. The finer the powder, the more beneficial it is to the performance of the microcrystalline glass.

[0047] S4: placing the basic glass powder in a mold and obtaining a glass-ceramic sample through a sample making machine, sintering the glass-ceramic sample, and obtaining the high-performance glass-ceramic after natural cooling.

[0048] In a specific embodiment, when preparing the original sample of microcrystalline glass, 0.5-1 mL of anhydrous ethanol or deionized water is added to the mold, and the mold is pressed for 10-15 seconds under a pressure of 8-10 MPa to obtain the original sample of microcrystalline glass.

[0049] In the above embodiment, the base glass powder can be moistened by adding anhydrous ethanol or deionized water into the mold for better compression molding.

[0050] In a specific embodiment, during sintering, the sintering is performed at 700-900° C. for 120-180 min. Optionally, when the aforementioned basic glass liquid only includes residual powder and phosphorus slag powder, the sintering is performed at 700-900° C. for 120-180 min; when the aforementioned basic glass liquid includes not only residual powder and phosphorus slag powder but also fly ash, the sintering is performed at 780-890° C. for 120-180 min.

[0051] In the present invention, the main components SiO2, Al2O3 and CaO in the oil-based rock cuttings de-oiling residue and the main components CaO, SiO2, Al2O3 and MgO (2% to 25%) in the phosphorus slag can be used to prepare CaO-Al2O3-SiO2 (CAS) microcrystalline glass or CaO-MgO-Al2O3-SiO2 (CMAS) microcrystalline glass. In the preparation process, CaO can act as a flux in the glass body as a complex oxide, providing a large amount of free oxygen to break the Si-O-Si bond, reduce the melting temperature of the glass, and reduce energy consumption; Al2O3 in the glass body acts as an intermediate oxide to increase the degree of polymerization in the glass structure; SiO2 is the main component of the glass body, and the [SiO4] tetrahedron it provides forms a large number of irregular network structures in the glass body to form a glass skeleton, which can effectively improve the various properties of the microcrystalline glass; in addition, MgO in the phosphorus slag can act as a glass network modifier to enhance the physical strength of the glass. At the same time, impurities such as Fe2O3, K2O, and P2O5 are also contained in the oil-based rock cuttings deoiling residue and phosphorus slag, which can be used as nucleating agents for microcrystalline glass to promote the nucleation and crystallization of microcrystalline glass. Based on the different MgO contents in the chemical composition of phosphorus slag, by adjusting the ratio of phosphorus slag to oil-based rock cuttings deoiling residue, CAS microcrystalline glass and CMAS microcrystalline glass can be prepared by using oil-based rock cuttings deoiling residue and phosphorus slag. When preparing CMAS microcrystalline glass, the content of SiO2 and Al2O3 in phosphorus slag is relatively low due to the high MgO content. The present invention uses fly ash to supplement SiO2 and Al2O3.

[0052] On the other hand, there is also provided a high-performance microcrystalline glass based on multi-source solid waste, which is prepared by using any one of the above-mentioned methods for preparing high-performance microcrystalline glass based on multi-source solid waste.

[0053] Example 1

[0054] A high-performance microcrystalline glass based on multi-source solid waste is prepared by the following steps:

[0055] (1) obtaining oil-based rock cuttings deoiling residue and phosphorus slag, and crushing, drying, ball milling and sieving the oil-based rock cuttings deoiling residue and the phosphorus slag respectively to obtain residue powder and phosphorus slag powder;

[0056] (2) performing component detection on the phosphorus slag powder, confirming the content of MgO in the phosphorus slag powder and preparing a basic glass liquid;

[0057] In this embodiment, the content of MgO in the phosphorus slag powder is less than 15% of the total mass of the phosphorus slag powder, and the residue powder and the phosphorus slag powder are mixed in a dry state at a mass ratio of 50:50, and after being evenly mixed, they are placed in a muffle furnace and heated to 1350° C. at 5° C. / min and kept warm for 180 min to obtain a basic glass liquid;

[0058] (3) immersing the basic glass liquid in water quenching to obtain basic glass, and drying, ball milling and sieving the basic glass to obtain basic glass powder;

[0059] In this embodiment, the drying is performed at 105° C. for 2 h and the particles are sieved using a 200-mesh sieve.

[0060] (4) placing the basic glass powder in a mold to obtain a glass-ceramic sample through a sample making machine, sintering the glass-ceramic sample, and obtaining the high-performance glass-ceramic after natural cooling;

[0061] In this embodiment, 3 g of basic glass powder is added with 0.5 mL of anhydrous ethanol with a mass fraction of 15% and loaded into the mold of a sample making machine. The microcrystalline glass sample is obtained under a pressure of 8 MPa for 10 seconds. The microcrystalline glass sample is then placed in a muffle furnace and heated to 890°C at 5°C / min and kept warm for 180 minutes. After cooling in the furnace, the high-performance microcrystalline glass (CAS series microcrystalline glass) is obtained.

[0062] Example 2

[0063] Different from Example 1, in step (2) of this example, the mass ratio of the residue powder to the phosphorus slag powder is 60:40.

[0064] Example 3

[0065] Different from Example 1, in step (2) of this example, the mass ratio of the residue powder to the phosphorus slag powder is 70:30.

[0066] Example 4

[0067] Different from Example 1, in step (2) of this example, the mass ratio of the residue powder to the phosphorus slag powder is 80:20.

[0068] Example 5

[0069] Different from Example 1, in step (2) of this example, the mass ratio of the residue powder to the phosphorus slag powder is 90:10.

[0070] Example 6

[0071] Different from Example 1, the mass ratio of the residue powder and the phosphorus slag powder in step (2) of this embodiment is 60:40; when sintering in step (4), the microcrystalline glass is placed in a muffle furnace as it is, first heated to 700°C at 5°C / min and kept warm for 90 min, then heated to 900°C at 5°C / min and kept warm for 90 min, and then cooled in the furnace to obtain the high-performance microcrystalline glass (CAS series microcrystalline glass).

[0072] Example 7

[0073] A high-performance microcrystalline glass based on multi-source solid waste is prepared by the following steps:

[0074] (1) obtaining oil-based rock cuttings deoiling residue and phosphorus slag, and crushing, drying, ball milling and sieving the oil-based rock cuttings deoiling residue and the phosphorus slag respectively to obtain residue powder and phosphorus slag powder;

[0075] (2) performing component detection on the phosphorus slag powder, confirming the content of MgO in the phosphorus slag powder and preparing a basic glass liquid;

[0076] In this embodiment, the content of MgO in the phosphorus slag powder is between 15% and 25% of the total mass of the phosphorus slag powder, and the residue powder and the phosphorus slag powder are mixed with fly ash in a dry state at a mass ratio of 40:10:50, and after being evenly mixed, they are placed in a muffle furnace and heated to 1450° C. at 5° C. / min and kept warm for 180 min to obtain a basic glass liquid;

[0077] (3) immersing the basic glass liquid in water quenching to obtain basic glass, and drying, ball milling and sieving the basic glass to obtain basic glass powder;

[0078] In this embodiment, the drying is performed at 105° C. for 2 h and the particles are sieved using a 200-mesh sieve.

[0079] (4) placing the basic glass powder in a mold to obtain a glass-ceramic sample through a sample making machine, sintering the glass-ceramic sample, and obtaining the high-performance glass-ceramic after natural cooling;

[0080] In this embodiment, 3 g of basic glass powder is added with 0.5 mL of anhydrous ethanol with a mass fraction of 15% and loaded into the mold of a sample making machine. The microcrystalline glass sample is obtained under a pressure of 8 MPa for 10 seconds. The microcrystalline glass sample is then placed in a muffle furnace and heated to 880°C at 5°C / min and kept warm for 180 minutes. After cooling in the furnace, the high-performance microcrystalline glass (CMAS series microcrystalline glass) is obtained.

[0081] Example 8

[0082] Different from Example 7, in step (2) of this example, the mass ratio of the residue powder and the phosphorus slag powder to the fly ash is 30:20:50.

[0083] Example 9

[0084] Different from Example 7, in step (2) of this example, the mass ratio of the residue powder and the phosphorus slag powder to the fly ash is 20:30:50.

[0085] Example 10

[0086] Different from Example 7, in step (2) of this example, the mass ratio of the residue powder and the phosphorus slag powder to the fly ash is 10:40:50.

[0087] Embodiment 11

[0088] Different from Example 7, the mass ratio of the residue powder and the phosphorus slag powder to the fly ash in step (2) of this embodiment is 20:30:50; during sintering in step (4), the microcrystalline glass is placed in a muffle furnace as it is, first heated to 780°C at 5°C / min and kept warm for 90 min, then heated to 890°C at 5°C / min and kept warm for 90 min, and then cooled in the furnace to obtain the high-performance microcrystalline glass (CMAS series microcrystalline glass).

[0089] Example 12

[0090] Different from Example 11, in step (3) of this embodiment, immersion quenching is not used for water quenching, but the base glass liquid is poured into water for rapid cooling quenching.

[0091] Comparative Example 1

[0092] Different from Example 2, a 60-mesh sieve was used for screening in step (3) of this comparative example.

[0093] Comparative Example 2

[0094] Different from Example 2, a 100-mesh sieve was used for screening in step (3) of this comparative example.

[0095] Comparative Example 3

[0096] A glass-ceramic is prepared by the following steps:

[0097] (1) obtaining oil-based rock cuttings deoiling residue, and crushing, drying, ball milling and sieving the oil-based rock cuttings deoiling residue to obtain residue powder;

[0098] (2) preparing basic glass liquid;

[0099] The residue powder is mixed with pure MgO reagent and fly ash in a dry state in a mass ratio of 42.5:7.5:50, and after being evenly mixed, the mixture is placed in a muffle furnace and heated to 1500° C. at a rate of 5° C. / min and kept at that temperature for 180 min to obtain a basic glass liquid;

[0100] (3) pouring the base glass liquid into water for rapid cooling and quenching to obtain base glass, and drying, ball milling and sieving the base glass to obtain base glass powder;

[0101] In this comparative example, the drying was carried out at 105°C for 2 hours and sieved with a 200-mesh sieve;

[0102] (4) placing the basic glass powder in a mold to obtain a glass-ceramic sample through a sample making machine, sintering the glass-ceramic sample, and obtaining the glass-ceramic after natural cooling;

[0103] In this embodiment, 3 g of basic glass powder is added with 0.5 mL of anhydrous ethanol with a mass fraction of 15% and loaded into the mold of a sample making machine. The microcrystalline glass sample is then placed in a muffle furnace and heated to 850°C at 5°C / min and kept warm for 90 min. The microcrystalline glass is then heated to 1000°C at 5°C / min and kept warm for 90 min. After cooling in the furnace, the microcrystalline glass (CMAS series microcrystalline glass) is obtained.

[0104] Comparative Example 4

[0105] Different from Comparative Example 3, the mass ratio of the residue powder to the pure MgO reagent and fly ash in step (2) of this comparative example is 45.5:4.5:50; during sintering in step (4), the microcrystalline glass is placed in a muffle furnace as it is, first heated to 800°C at 5°C / min and kept warm for 90 min, then heated to 950°C at 5°C / min and kept warm for 90 min, and then cooled in the furnace to obtain the microcrystalline glass (CMAS series microcrystalline glass).

[0106] The performance of the glass-ceramics obtained in the above embodiments and comparative examples was tested, and the test results are shown in Table 1:

[0107] Table 1 Performance test results of glass-ceramics of various embodiments and comparative examples

[0108]

[0109]

[0110] It can be seen from Table 1 that the CAS-based glass-ceramics and CMAS-based glass-ceramics obtained in each embodiment of the present invention have good performance and can meet the requirements of the standard "Industrial Microcrystalline Plate" JC / T 2097-2011; since the main crystalline phases of the CMAS-based glass-ceramics prepared in the present invention are pyroxene and pyroxene, their hardness is greater than that of wollastonite, the main crystalline phase of CAS-based glass-ceramics, and therefore the CMAS-based glass-ceramics have higher flexural strength than CAS-based glass-ceramics; the melting temperature of CAS-based glass-ceramics is lower than that of CMAS-based glass-ceramics; in addition, by comparing Example 11 and Example 12, it can be seen that the glass-ceramics prepared by immersion water quenching has higher flexural strength than the glass-ceramics obtained by rapid cooling water quenching, and other properties are also more advantageous.

[0111] By comparing Example 2 of the present invention with Comparative Examples 1 and 2, it can be seen that the basic glass powder obtained by screening with 60-mesh and 100-mesh sieves is too coarse (particle size is greater than 0.075 mm), and the obtained microcrystalline glass has low density and acid and alkali corrosion resistance, and high water absorption, which cannot meet the requirements of the standard "Industrial Microcrystalline Plate" JC / T 2097-2011.

[0112] By comparing Example 11 of the present invention with Comparative Example 3 (the amount of pure MgO reagent was calculated based on the MgO content of 25% in the phosphorus slag powder of Example 11) and Comparative Example 4 (the amount of pure MgO reagent was calculated based on the MgO content of 15% in the phosphorus slag powder of Example 11), it can be seen that the various properties of the CMAS series microcrystalline glass prepared by using pure MgO reagent are inferior to the various properties of the CMAS series microcrystalline glass prepared by Example 11 of the present invention, and the sintering temperature adopted in Example 11 of the present invention is lower.

[0113] In addition, the heavy metal concentration and related indicators in the microcrystalline glass leachate of the present invention are far lower than the "Comprehensive Sewage Discharge Standard" (GB 8978-1996) and the "Hazardous Waste Identification Standard Leaching Toxicity Identification" (GB 5085.3-2007), and will not cause secondary pollution to the environment, thus realizing the coordinated harmless treatment and high-value utilization of multi-source solid waste.

[0114] In summary, the present invention can prepare glass-ceramics with excellent performance that meets the requirements of the standard "Industrial Microcrystalline Plate" (JC / T 2097-2011) without adding additional nucleating agents, by using two solid wastes, namely, oil-based rock cuttings deoiling residue and phosphorus slag. Compared with the prior art, the present invention has significant progress.

[0115] The above descriptions are only representative embodiments of the present invention and are not intended to limit the present invention in any form. Any technician familiar with the profession who makes slight changes or modifications to the embodiments using the above disclosed technical contents without departing from the scope of the technical solution of the present invention are equivalent embodiments of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing high-performance glass-ceramics based on multi-source solid waste, characterized in that: The following steps are involved: S1: obtaining oil-based rock cuttings deoiling residue and phosphorus slag, and crushing, drying, ball milling and sieving the oil-based rock cuttings deoiling residue and the phosphorus slag respectively to obtain residue powder and phosphorus slag powder; S2: performing component detection on the phosphorus slag powder to confirm the content of MgO in the phosphorus slag powder; If the content of MgO in the phosphorus slag powder is less than 15% of the total mass of the phosphorus slag powder, the residual powder and the phosphorus slag powder are mixed, and after being evenly mixed, they are melted to obtain a basic glass liquid; If the content of MgO in the phosphorus slag powder is less than 25% and greater than or equal to 15% of the total mass of the phosphorus slag powder, the residual powder and the phosphorus slag powder are mixed with fly ash, and the mixture is uniformly mixed and then melted to obtain a basic glass liquid; S3: quenching the basic glass liquid to obtain basic glass, and drying, ball-milling and sieving the basic glass to obtain basic glass powder; S4: placing the basic glass powder in a mold and obtaining a glass-ceramic sample through a sample making machine, sintering the glass-ceramic sample, and obtaining the high-performance glass-ceramic after natural cooling.

2. The method for preparing high-performance glass-ceramics based on multi-source solid waste according to claim 1, characterized in that: In step S1, screening is performed using a sieve with a mesh size of 200 or more.

3. The method for preparing high-performance glass-ceramics based on multi-source solid waste according to claim 1, characterized in that: In step S2, when mixing, the amount of each raw material used is 10-90 parts of residue powder, 10-50 parts of phosphorus slag powder, and 0-50 parts of fly ash, respectively, by weight.

4. The method for preparing high-performance glass-ceramics based on multi-source solid waste according to claim 1, characterized in that: In step S2, during melting, the temperature is raised to 1350-1450°C at a rate of 5-7°C / min and kept at this temperature for 150-180 min.

5. The method for preparing high-performance glass-ceramics based on multi-source solid waste according to claim 1, characterized in that: In step S3, water quenching is performed by an immersion water quenching method.

6. The method for preparing high-performance glass-ceramics based on multi-source solid waste according to claim 1, characterized in that: In step S3, when water quenching is performed, the product is quenched in cold water at 10-20° C. for 5-10 minutes; when drying is performed, the product is dried at 100-105° C. for 2-3 hours.

7. The method for preparing high-performance glass-ceramics based on multi-source solid waste according to claim 1, characterized in that: In step S3, screening is performed using a sieve with a mesh size of 200 or more.

8. The method for preparing high-performance glass-ceramics based on multi-source solid waste according to claim 1, characterized in that: In step S4, when preparing the original sample of the microcrystalline glass, 0.5-1 mL of anhydrous ethanol or deionized water is added to the mold, and the mold is pressed for 10-15 seconds under a pressure of 8-10 MPa to obtain the original sample of the microcrystalline glass.

9. The method for preparing high-performance glass-ceramics based on multi-source solid waste according to any one of claims 1 to 8, characterized in that: In step S4, sintering is performed at 700-900° C. for 120-180 min.

10. A high-performance glass-ceramic based on multi-source solid waste, characterized in that: The high-performance microcrystalline glass is prepared by the method for preparing high-performance microcrystalline glass based on multi-source solid waste as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing glass ceramics

    CN105731808A

  • High-strength low-density ceramsite proppant and preparation method thereof

    CN117776681A